Dampak Penggunaan Gadget Terhadap Prilaku Sosial Anak Usia Sekolah Dasar - Rahayu Sri Utami Utami; Mia Ardelina Finci Haloho; Kevin Tambunan; Miahi Maria Sinaga (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2022)
This study aims to the impact of using gadgets on the social behavior of elementary school-aged children aged 10 years and parents’ efforts to overcome the negative impacts of using gadgets. Sosial behavior is a person’s action which is the result of the relationship between individuals and the surrounding enviroment which is a response to their social enviroment. Humans are sosial creature who cannot live alone, but desperately need help from other. A gadget is an electronic device that has a special function and the surrounding environment which is a response to their social enviroment. Humans are social creatures who cannot live alone, but desperately need help from other. A gadget is an electronic device that has a speacial funcation and is practical in its use. This reasearch is a qualitative descriptive data analysis. The results show that the use of gadgets has a negative and positive impact. The negative impact is that the child will be less active in socializing and less physically active. The positive impact is facilitating communication, media for children’s entertaiment, increasing comfort in learning, increasing knowledge. Efforts to overcome the negative impact of using gadget are that parents need to have an understanding of gadget, provide, provide direction, provide understanding, give advice to children, limit children in using gadgets.